Relationship between atherogenic index of plasma, asprosin, and metrnl levels in hemodialysis patients - Yardim, Meltem; Deniz, Levent; Saltabas, Mehmet Akif; Kayalp, Damla; Akkoc, Ramazan Fazil; Kuloglu, Tuncay (Kare Publ, 2024)
Objectives: This study aimed to evaluate the relationship between the atherogenic index of plasma (AIP) and plasma asprosin and metrnl levels in hemodialysis (HD) patients. Methods: Forty-eight patients receiving HD treatment with a diagnosis of end-stage renal disease (ESRD) were included.The control group comprised 34 age-, sex-, and body mass index-matched healthy volunteers without a history of renal disease. ESRD patients were divided into two groups: high-risk (AIP >= 0.24) and low-moderate risk (AIP<0.24). Asprosin and metrnl levels in the plasma of blood samples taken just before dialysis were studied by enzyme-linked immunosorbent assay. Results: A significant difference was found between the control group [23.3(19.9-27.7 ng/mL)], the low-moderate risk group [39.3(34.9-40.8 ng/mL)], and the high-risk group [48.1(44.5-49.9 ng/mL)] in terms of asprosin levels (for each p<0.001). Asprosin values of both low-moderate risk and high-risk groups were significantly higher than the controls. In the high-risk group, plasma asprosin levels were higher than in the low-moderate risk group (p=0.012). Metrnl levels of the high-risk group were found to be lower than both the control and low-risk groups (p<0.001 and p=0.003, respectively). AIP showed a positive relation to asprosin and a negative relation to metrnl. Conclusion: Logistic regression analysis has revealed important insights into the independent relationships between metrnl, asprosin, and high AIP values in HD patients. These findings support the anti-atherogenic potential of metrnl and suggest the potential atherogenic effects of asprosin, highlighting the complex interplay between adipokines and cardiovascular risk in this
Keywords: Adipokine; asprosin; atherogenic index of plasma; hemodialysis; meteorin-like protein